EDUCATIONAL BLOG AND THE TEACHING OF FOLK DANCES IN PHYSICAL EDUCATION CLASSES: APPROACHES FROM THE SAO PAULO STATE CURRICULUM - Santos Diniz, Irlla Karla dos [UNESP]; Darido, Suraya Cristina (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2015)
The aim of this study was to develop and evaluate supplementary teaching materials to the curriculum of Physical Education of the State of Sao Paulo in the form of educational blog of folk dances. A qualitative survey was conducted in three steps: documentary analysis of curriculum in relation to dance, blog production, and evaluation by teachers. The blog was indicated as a continuing training tool enabling quick access and gathering various media in the same virtual space. However, limitations were identified in the use of this tool for the organization of dance knowledge, the school structure and the conditions of teaching.
Keywords: Physical Education; Dance; Blog; Curriculum